Kompetitif Bisnis Kerajinan Batik - Nuruddin Armanto (Fakultas Ekonomi dan Bisnis Islam, 2015)
In this research, Kopontren discuss the idea of Kopontren role in empowering peoples economy empowerment programs through the loan and save it for the society stores / minimarts, also using a cyber cafe to people about boarding finally can be achieved with both the welfare of the surrounding community and Kopontren where Kopontren has strategic role in the increased business as a member of islamic cooperation that, and good management of the savings from the bank capital. However, there are some people who think that Pesisir Kopontren still unable to provide maximum service and business services for residents. The research that we use is a case study in Kopontren Miftahul Ulum Pesisir with the actual data in the interview techniques (interview) and direct observation. Besides, we also use of the library to become as a reference for research. It appears that the success of the business Kopontren Miftahul Ulum the loan and save is this program could provide a solution to develop business in a run by members of the public to empower villagers Pesisir in order to become partners Kopontren Miftahul Ulum. Therefore comes a business model Kopontren project program through an increase in loan and save to improve services, and cyber cafe and also to increase distribution to the minimarts in hopes can become an inspiration for the parties involved and cooperatives (Kopontren) in the field.